The moderator role of corporate governance on capital structure-performance nexus: Evidence from Sub-Saharan Africa - Isaac Bawuah (Cogent Business & Management, 2024)
This paper examines the moderator role of the corporate governance (CG) mechanism (board size, board independence, board gender diversity, board meetings, board ownership and institutional ownership) in the capital structure (CS) - Firm performace (FP) nexus using country - and firm - level data for a sample of 100 firms in 7 Sub-Saharan African countries over 2010–2020. In addition, the paper investigates the direct effects of CS on FP. Employing the two-step system generalised methods of moments estimator, this paper extends, as well as offers fresh evidence to current literature. First, the evidence shows that firms with long-term leverage achieve higher performance measured with ROE. However, the findings also show that short-term leverage and total leverage are significantly associated with lower performance measured with ROA, ROE and Tobin's Q. Further, the empirical results reveal that total leverage complements CG mechanism of board independence, board gender diversity, board meetings, managerial ownership and institutional ownership to induce positive and significant effects on FP, with the association being stronger for diverse boards (gender and non-executive directors) and institutional ownership, meanwhile, board size induces a negative association between total leverage and FP. Thus, the results suggest that the CG mechanisms play a positive and significant moderator role between CS and FP. Also, assets tangibility, growth opportunities, financial development and economic growth drive FP. The results are robust to possible endogeneity problems arising from simultaneous issues using the lagged structure and fixed effects methods.
Keywords: 650; Corporate governance; capital structure; firm performance; Sub-Saharan Africa